20 QUESTIONS A SOCIOLOGIST SHOULD ASK ABOUT POLL RESULTS - Gawiser, Sheldon R.; Witt, G. Evans (La Sociología en sus Escenarios, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Resumen. Las encuestas proporcionan la mejor fuente de información directa sobre la opinión pública. Son herramientas valiosas para los sociólogos y pueden servir como la base para el análisis de situaciones sociales. Para el sociólogo que analiza una batería de datos cuantitativos, aquí se le plantea que tenga en cuentas estas veinte observaciones metodológicas y de sentido común antes de entregar sus análisis e interpretaciones de los resultados de sus estudios. Abstract. Polls provide the best direct source of information about public opinion. They are valuable tools for Sociologists and can serve as the basis for accurate, informative news stories. For the Sociologist looking at a set of poll numbers, here are the 20 questions to ask the pollster before reporting any results. This publication is designed to help working Sociologists do a thorough, professional job covering polls. It is not a primer on how to conduct a public opinion survey.